Alteration in neuromuscular function after a 5 km running time trial - Girard, O.; Millet, G. P.; Micallef, J. P.; Racinais, S. (European Journal of Applied Physiology, 2012)
The aim of this study was to characterize the effect of a 5 km running time trial on the neuromuscular properties of the plantar flexors. Eleven well-trained triathletes performed a series of neuromuscular tests before and immediately after the run on a 200 m indoor track. Muscle activation (twitch interpolation) and normalized EMG activity were assessed during maximal voluntary contraction (MVC) of plantar flexors. Maximal soleus H-reflexes and M-waves were evoked at rest (i.e. H MAX and M MAX, respectively) and during MVC (i.e. H SUP and M SUP, respectively). MVC significantly declined (-27%; P < 0.001) after the run, due to decrease in muscle activation (-8%; P < 0.05) and M MAX-normalized EMG activity (-13%; P < 0.05). Significant reductions in M-wave amplitudes (M MAX: -13% and M SUP: -16%; P < 0.05) as well as H MAX/M MAX (-37%; P < 0.01) and H SUP/M SUP (-25%; P < 0.05) ratios occurred with fatigue. Following exercise, the single twitch was characterized by lower peak torque (-16%; P < 0.001) as well as shorter contraction (-19%; P < 0.001) and half-relaxation (-24%; P < 0.001) times. In conclusion, the reduction in plantar flexors strength induced by a 5 km running time trial is caused by peripheral adjustments, which are attributable to a failure of the neuromuscular transmission and excitation-contraction coupling. Fatigue also decreased the magnitude of efferent motor outflow from spinal motor neurons to the plantar flexors and part of this suboptimal neural drive is the result of an inhibition of soleus motoneuron pool reflex excitability.